S31. ENHANCEMENT OF SYNAPTIC PLASTICITY BY COMBINATION OF PDE2 AND PDE9 INHIBITION PRESUMABLY VIA PRE- AND POST-SYNAPTIC MECHANISMS. (18th May 2020) - Rosenbrock, Holger; Kroker, Katja; Stierstorfer, Birgit; Hobson, Scott; Arban, Roberto; Dorner-Ciossek, Cornelia
Abstract: Background: Evidence from clinical and preclinical studies has led to the hypothesis that impaired glutamatergic transmission and NMDA receptor hypofunction play an important role in cognitive impairment associated with schizophrenia (CIAS). Second messenger pathways depending on cAMP and/or cGMP are key regulators of glutamatergic transmission and NMDA receptor related pathways. Therefore, the specific cyclic nucleotide phosphodiesterases (PDEs) PDE2 and PDE9, expressed in cognition relevant brain regions such as cortex and hippocampus, are putative targets for cognition enhancement in neuropsychiatric disorders (Dorner-Ciossek et al., 2017; Zhang et al., 2017). In fact, it has previously been shown that either PDE2 or PDE9 inhibition increases synaptic plasticity, as determined by hippocampal long-term potentiation (LTP), and improves memory performance in animal cognition tasks. However, the exact sub-cellular localization of PDE2 and PDE9 enzymes in neurons is not fully established. Thus, in the present study, co-localization studies of PDE2 and PDE9 with pre- and post-synaptic markers were performed by double immunofluorescence staining. Moreover, the PDE2 inhibitor PF-05180999 (Helal et al., 2018) was characterized regarding enhancement of hippocampal LTP and further investigated in combination with the PDE9 inhibitor Bay 73–6691 (Wunder et al., 2005) for potential synergistic effects on LTP. Methods: Brains of adult rats were fixed with formalin and sliced for double immunofluorescence staining of PDE2 or PDE9 enzymes with pre-/post-synaptic markers. Analysis of staining was performed by confocal microscopy. Effects of the PDE2 inhibitor PF-05180999 alone and in combination with the PDE9 inhibitor Bay 73–6691 on synaptic plasticity were evaluated in rat hippocampal slices by using a protein-synthesis independent early LTP paradigm. Results: Double immunofluorescence analysis revealed co-localization of PDE2 predominantly with pre-synaptic, but not post-synaptic, markers and mainly in glutamatergic neurons. In contrast, PDE9 showed co-localization with post-synaptic markers. Inhibition of PDE2 by PF-05180999 led to a concentration-dependent enhancement of early LTP. Combination of PF-05180999 with a subthreshold concentration of the PDE9 inhibitor Bay 73–6691 caused a transformation from early LTP into protein-synthesis dependent late LTP. Discussion: Immunofluorescence staining suggests that PDE2 is localized pre-synaptically in glutamatergic neurons. This might indicate an involvement of PDE2 in neurotransmitter release via regulating cGMP/cAMP levels at pre-synaptic terminals, whereas PDE9 is located post-synaptically presumably involved in the NMDA receptor signaling cascade via regulation of cGMP. Corroborating previous findings, PDE2 inhibition improves synaptic plasticity as shown by enhanced LTP. Moreover, for the first time, we could show that the combination of a PDE2 with a PDE9 inhibitor acts synergistically on improvement of synaptic plasticity as demonstrated by the shift from early into late LTP, which is considered to be a crucial mechanism for memory formation. References: Dorner-Ciossek et al. (2017), Adv. Neurobiol. 17, 231–254. Helal et al. (2018), J. Med. Chem. 61, 1001–1018. Wunder et al. (2005), Mol.Pharmacol. 68, 1775–1781. Zhang et al. (2017), Adv. Neurobiol. 17, 307–347.